Risk factors associated with quad bike crashes: a protocol for systematic review of observational studies - Menon, Preetha; EI-Sadig, Mohamed; AB Khan, Moien; Östlundh, Linda; El-Deyarbi, Marwan; Al-Rifai, Rami H; Grivna, Michal (BMJ open, 2021)
IntroductionQuad bikes are four-wheeled vehicles, driven off-road on uneven terrains by farmers for work or young adults for leisure. Quad bike accidental crashes result mostly due to the unique ecosystem of uneven terrain, where these unstable vehicles are commonly driven, in addition to numerous distinctive sociodemographic characteristics related to drivers. This is a protocol for a systematic review of observational studies from all geographical regions and demographic groups in the world to summarise the common risk factors relating to quad bike crashes.Methods and analysisA comprehensive search for the literature on quad bike crashes and related injuries will be conducted in six electronic databases: PubMed, Embase, Scopus, Web of Science, IEEE and PsycINFO. Proquest Dissertation and Thesis, OpenGrey and BASE will be searched for grey literature. Five researchers will be involved in the screening, and the review of full text articles, using the inclusion and exclusion criteria. Disagreements between reviewers will be resolved by discourse. Three researchers will help resolving conflicts that may arise during the screening process and will resolve eventual conflicts identified in the process with the help of the systematic review software ’Covidence’ for automatic deduplication and blinded screening. Information on crashes leading to injuries and death, target population characteristics and risk factors involved will be extracted from eligible articles in addition to the assessment of the quality of the researched articles.Ethics and disseminationSince this is a systematic review of published literature, a formal ethical approval is not needed. Results of the review will be disseminated through peer-reviewed publications, conference presentations and reports to the concerned authorities.PROSPERO registration numberCRD42020170245.